Analysis Of The Application Of Merle H. Mishel's Theory: Uncertainty In Illness Theory In Patients With Colon Cancer Cases - Amami Amami; Irna Nursanti (The Journal General Health and Pharmaceutical Sciences Research, 2024)
Introduction: Mishel's Theory of Uncertainty in Illness offers insights into how patients navigate uncertainty in health contexts. This study examines its application in individuals with colon cancer.Methods: Literature review and case study analysis were employed to explore Mishel's theory's relevance in colon cancer care.Results: Mishel's theory provides a framework for understanding and addressing uncertainty among colon cancer patients. Nursing interventions focusing on education, social support, and coping strategies facilitate patient adaptation.Conclusion: Mishel's Theory of Uncertainty in Illness enhances nursing practice by guiding interventions tailored to address uncertainty in colon cancer patients. Integrating this framework fosters patient understanding and coping, ultimately improving quality of care and patient outcomes.